Apple Inc Advertising Strategy - Rd Rafaida Putri Rahmania W (Journal of Accounting and Finance Management, 2022)
This study aims to find out the results of an analysis of Apple Inc. in developing its marketing advertising strategy, especially related to the increase in advertising that is Apple's trademark. The method used in this study uses qualitative research methods and literature review. The results of this study indicate that Apple adapts User Generated Content (UGJ) to promote its products on social media, namely product placement on influencers/public figures, which are commonly called endorsements and "buzz" generated by positive reviews in the media. Apple nonetheless created a simple promotional concept that led to loyal customers with an unprecedented market share. Even the products themselves are kept sleek and minimal, with simple color schemes and clean, uncluttered designs.